Malay lexical borrowings in Singapore colloquial English - Buang, Sri Norazrin; Halim, Nurulhuda Abdul; Ramakresinin, Shamala (Journal of Modern Languages, 2017)
Singapore English evolved as a contact variety with English as its superstrate and the local languages, namely Chinese, Malay and Tamil as its substrate languages. It is expected, therefore, that Singapore English would contain features borrowed from these substrate languages. In this paper, we investigate the processes and types of lexical borrowing in the colloquial variety of Singapore English (henceforth SCE) from vernacular Malay. Based on analysis carried out on a corpus of sixty-four Malay ISCE lexical items, we propose that equivalence in the grammatical category, economy of use and social motivations are three key factors that could account for the integration of Malay words in SCE. In addition, the integration of Malay words in SCE works in tandem with the more dominant substrates influence of Chinese languages on the grammar of SCE.